Utilização de altas concentrações de benzeno, tolueno e xileno (compostos BTX) como fonte de carbono por linhagens bacterianas - Dulcini, Silvana Elizabeth de Méo (Universidade Federal de São Carlos, 2002)
BTX compouds [benzene, toluene and xylene isomers (ortho, meta and para)] are light aromatics present in gasoline. They are toxic and relatively soíuble in water. This high solubility in comparison with other petroleum hydrocarbons explains their potential effect in the environment. Experimenta with pre-conditionated cultures, isolated from petroleum contaminated sites, were carried out with the aim of selecting sotventtolerant strains able of growing in high concentrations of BTX. Those strains were evaluated for their ability of p-xylene utilization. After 3 days of incubation, two strains were responsible for high percentages of pxylene removal from culture médium. It was concluded that these results were related to biodegradation, since the strains were able to grow in pxylene as the sole source of carbon and energy. High performance liquid chromatography and gas chromatography with flame ionization detection were used for BTX-determinationsr Biosurfactant production from the cultures was also evaluated, by emulsifying activity and emulsifying index (E24) determinations. Emulsification did not showany relationship with pxylene biodegradation.
Keywords: Biodegradação; Bactérias; Benzeno; Tolueno; Xileno; CIENCIAS BIOLOGICAS::ECOLOGIA